2009
DOI: 10.1039/b913068c
|View full text |Cite
|
Sign up to set email alerts
|

Palladium complexes of abnormal N-heterocyclic carbenes as precatalysts for the much preferred Cu-free and amine-free Sonogashira coupling in air in a mixed-aqueous medium

Abstract: A series of new PEPPSI (Pyridine Enhanced Precatalyst Preparation Stabilization and Initiation) themed precatalysts of abnormal N-heterocyclic carbenes for the highly desirable Cu-free and amine-free Sonogashira coupling in air in a mixed-aqueous medium is reported. Specifically, the PEPPSI themed (NHC)PdI2(pyridine) type precatalysts, 1b-4b, efficiently carried out the highly convenient Cu-free and amine-free Sonogashira coupling of aryl bromides and iodides with terminal acetylenes in air in a mixed aqueous … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
58
1
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 132 publications
(64 citation statements)
references
References 100 publications
4
58
1
1
Order By: Relevance
“…Quite significantly, several of the trans-[(NHC) 2 PdX 2 ] (X = halide) (compounds 7, [39] 16, 17 [57] ), cis-[(NHC) 2 PdCl 2 ] (8), [39] trans-[(NHC)PdX 2 (pyridine)] (compounds 1, [39] 9, [39] 10-15, [58] 18, [57] 19, [57] 21-24 [32] ) and chelating-[(NHC)-PdCl 2 ] (20) types of complexes showed activity towards the Sonogashira coupling under the desired amine-free [39] and the both amine-free and Cu-free conditions [32,57,58] (Figures 2 Having again observed that the more electron-rich metal center in cis-and trans-[(NHC) 2 PdX 2 ] type complexes fare better than the less electron-rich centers in trans-[(NHC)-PdX 2 (pyridine)] type compounds, we shifted our focus to a more electron-rich, so-called "abnormal N-heterocyclic carbene ligands". The abnormal N-heterocyclic carbene ligands, by virtue of the carbene center's being flanked by just one heteroatom, as opposed to two in the normal Nheterocyclic carbene ligands, are considered more electronrich than their normal N-heterocyclic carbene counterparts.…”
Section: Sonogashira Cross-coupling Reactionsmentioning
confidence: 83%
“…Quite significantly, several of the trans-[(NHC) 2 PdX 2 ] (X = halide) (compounds 7, [39] 16, 17 [57] ), cis-[(NHC) 2 PdCl 2 ] (8), [39] trans-[(NHC)PdX 2 (pyridine)] (compounds 1, [39] 9, [39] 10-15, [58] 18, [57] 19, [57] 21-24 [32] ) and chelating-[(NHC)-PdCl 2 ] (20) types of complexes showed activity towards the Sonogashira coupling under the desired amine-free [39] and the both amine-free and Cu-free conditions [32,57,58] (Figures 2 Having again observed that the more electron-rich metal center in cis-and trans-[(NHC) 2 PdX 2 ] type complexes fare better than the less electron-rich centers in trans-[(NHC)-PdX 2 (pyridine)] type compounds, we shifted our focus to a more electron-rich, so-called "abnormal N-heterocyclic carbene ligands". The abnormal N-heterocyclic carbene ligands, by virtue of the carbene center's being flanked by just one heteroatom, as opposed to two in the normal Nheterocyclic carbene ligands, are considered more electronrich than their normal N-heterocyclic carbene counterparts.…”
Section: Sonogashira Cross-coupling Reactionsmentioning
confidence: 83%
“…Complexes which allow for electron delocalization are betteracceptors granting the Ir C bond greater double bond character. Similar palladium complexes could be synthesized by Ghosh and co-workers for use as precatalysts in Sonogashira coupling reactions [44].…”
Section: Figmentioning
confidence: 97%
“…[16] Although a high yield of this product was recently reported by Sonogashira coupling, an unusual N-heterocyclic carbene precatalyst was required, which has a complicated structure and requires a multistep synthesis. [17] Some other -CHO group-containing products were also prepared in good to high yields, the results indicating that -CHO group can facilitate the cross coupling reaction in this system. In the Sonogashira reaction, the acetylene subunit of the diarylacetylene comes from the nucleophile, whereas with our method the acetylene subunit comes from the electrophile.…”
mentioning
confidence: 94%